Feminist epistemologies - Alcoff, Linda Martín.; Potter, Elizabeth (Thinking gender, 1993)
Il s'agit de la première collection de théoriciennes féministes influentes à se concentrer sur le cœur de l'épistémologie traditionnelle, traitant de questions telles que la nature des connaissances et l'objectivité dans une perspective de genre.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; point de vue situé; ressource en ligne; sciences humaines; thématiques; épistémologie

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Whose science? Whose knowledge?: Thinking from women's lives - Harding, Sandra G. (Science question in feminism, 1991)
Sandra Harding here develops further the themes first addressed in her widely influential book, The Science Question in Feminism, and conducts a compelling analysis of feminist theories on the philosophical problem of how we know what we know.Following a strong narrative line, Harding sets out her arguments in highly readable prose. In Part 1, she discusses issues that will interest anyone concerned with the social bases of scientific knowledge. In Part 2, she modifies some of her views and then pursues the many issues raised by the feminist position which holds that women's social experience provides a unique vantage point for discovering masculine bias and and questioning conventional claims about nature and social life. In Part 3, Harding looks at the insights that people of color, male feminists, lesbians, and others can bring to these controversies, and concludes by outlining a feminist approach to science in which these insights are central. "Women and men cannot understand or explain the world we live in or the real choices we have," she writes, "as long as the sciences describe and explain the world primarily from the perspectives of the lives of the dominant groups."Harding's is a richly informed, radical voice that boldly confronts issues of crucial importance to the future of many academic disciplines. Her book will amply reward readers looking to achieve a more fruitful understanding of the relations between feminism, science, and social life.
Keywords: approches et analyses; cours; discipline; fem1000; point de vue situé; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; épistémologie